The Effect of Minimum Wages, Investment, and Regional Gross Domestic Product on Labor Absorption in West Nusa Tenggara 2010-2025 - Nasir Sungkar; Busaini Busaini; Akhmad Jufri (JURNAL ECONOMINA, 2026)
ABSTRACK Labor absorption is a key indicator of the success of regional economic development, as it reflects the economy’s ability to provide employment opportunities for the productive-age population. This study aims to determine the effect of minimum wages, investment, and gross regional domestic product (GRDP) on labor absorption in West Nusa Tenggara from 2010 to 2025. Thus study employed obtained from the West Nusa Tenggara Central Statistics Agency (BPS), the West Nusa Tenggara Province Investment and One-Stop Integrated Service Office, and the West Nusa Tenggara Manpower and Transmigration Office. The result indicate that minimum wages and investment have a positive and significant effect an labor absorption. In contrast, GRDP has a positive but insignificant effect on labor absorption. Based on these findings, it is recommended that local government promote inclusive economic growth oriented toward job creation, maintain consistent minimum wage policies that support labor welfare and productivity, and direct investment to labor-intensive sector based on local potential to increase labor absorption sustainably.